210Pb mass accumulation rates in the depositional area of the Magra River (Mediterranean Sea, Italy). (1st August 2016) - Delbono, I.; Barsanti, M.; Schirone, A.; Conte, F.; Delfanti, R.
Abstract: Nine sediment cores were collected between 2009 and 2012 in the inner continental shelf (Mediterranean Sea, Italy) mainly influenced by the Magra River, at water depths ranging from 11 to 64 m. Mass Accumulation Rates (MARs) were calculated through 210 Pb analysed by Gamma spectrometry. Three different dating models (single and two-layer CF-CS, CRS) were applied to clay normalised 210 Pbxs profiles and 137 Cs was used to validate the 210 Pb geochronology. The maximum MAR values (>2 g cm −2  yr −1 ) were found in the region adjacent to the Magra River mouth and outside the Gulf of La Spezia (0.9±0.1 g cm −2  yr −1 at St. 3-C6 and 4-C4). Results from 137 Cs/ 210 Pbxs ratios calculated in Surface Mixed Layers (SMLs) evidenced the coastal boundaries of the Magra River depositional area, which is very limited towards south. Differently, in the north-west sector, fine sediments are generally driven by the Ligurian Current and move towards north-west: at the deepest and most distant station from the River mouth, the MAR value is the lowest one in the study area. Few major Magra River floods occurred during the sediment core sampling period. By using the short-lived radioisotope 7 Be as a tracer of river floods, a clear 7 Be signature of 2009 flood is present at St. 1-SA1C. Finally, by analyzing the clay normalised 210 Pbxs profiles, a decrease of its activity dating the years 1999 and 2000 is observed in four cores, corresponding to two major Magra River floods occurring in those years. Highlights: MARs calculated with three dating models and geochronology validation by 137 Cs peak. 137 Cs/ 210 Pbxs delimits the coastal boundaries of the Magra River depositional area. 2009 flood marked by 7 Be downcore profile near the Magra River mouth. 1999 and 2000 floods traced by 210 Pbxs depletion in four sediment cores.